Fumaric acid ester‐induced T‐cell lymphopenia in the real‐life treatment of psoriasis. (28th February 2019) - Dickel, H.; Bruckner, T.; Höxtermann, S.; Dickel, B.; Trinder, E.; Altmeyer, P.
Abstract: Background: Fumaric acid esters (FAEs) are used to treat psoriasis and are known to cause lymphopenia in roughly 60% of the patients. Much remains to be elucidated about the biological effects of FAEs on lymphocytes. Objective: To evaluate the influence of long‐term FAE (Fumaderm ® ) treatment on peripheral blood CD4 + and CD8 + T cells, CD19 + B cells and CD56 + natural killer (NK) cells in psoriasis. Methods: In this single‐centre retrospective observational subcohort study, we obtained leucocyte and lymphocyte subset counts before initiating FAE therapy in 371 psoriasis patients (mean age, 47.8 years; 63.3% males) and monitored them during treatment (mean treatment duration, 2.9 years). Multiparametric flow cytometry was used for immunophenotyping. Results: FAEs significantly reduced the numbers of CD4 + T, CD8 + T, CD19 + B and CD56 + NK cells. Among lymphocyte subsets, the mean percentage reduction from baseline was always highest for CD8 + T cells, with a peak of 55.7% after 2 years of therapy. The risk of T‐cell lymphopenia increased significantly with the age of the psoriasis patients at the time that FAE therapy was initiated. It was significantly decreased for the combination therapy with methotrexate and folic acid (vitamin B9) supplementation. Supporting evidence was found suggesting that T‐cell lymphopenia enhances the effectiveness of FAE therapy. Conclusions: Monitoring distinct T‐cell subsets rather than just absolute lymphocyte counts may provide more meaningful insights into both the FAE treatment safety and efficacy. We therefore suggest optimizing pharmacovigilance by additionally monitoring CD4 + and CD8 + T‐cell counts at regular intervals, especially in patients of middle to older age. Thus, further prospective studies are needed to establish evidence‐based recommendations to guide dermatologists in the management of psoriasis patients who are taking FAEs and who develop low absolute T‐cell counts.